2014
DOI: 10.5465/ambpp.2014.247
|View full text |Cite
|
Sign up to set email alerts
|

A Place for Emotion: How Space Structures Nurse-Parent Interactions in W. African Pediatric Wards

Abstract: A wide range of workers are regularly tasked with managing their own and others' negative emotions. Existing literature provides a number of strategies for doing so, but is based largely on organizational settings that share certain key characteristics. Using observational and interview data from a very different setting, high-mortality pediatric hospital wards in West Africa, I find that despite widely-shared norms to the contrary, nurses are twice as likely to respond to emergencies and patient deaths with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 77 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…But what remains undertheorized is how physical space can produce relational consequences in organizations, affecting everyday employee work behaviors (Elsbach and Pratt, 2007;Harvey, 2010). I build on recent relational studies of physical space (Elsbach, 2003;Millward, Haslam, and Postmes, 2007;Kellogg, 2009;Bernstein, 2012;Manning, 2014), illustrating how changes in the configuration of space can disrupt and transform extant social practices in organizations with important consequences for temporal flexibility. This study thus offers additional empirical evidence of a relationship among physical space, social practices, and social cognition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But what remains undertheorized is how physical space can produce relational consequences in organizations, affecting everyday employee work behaviors (Elsbach and Pratt, 2007;Harvey, 2010). I build on recent relational studies of physical space (Elsbach, 2003;Millward, Haslam, and Postmes, 2007;Kellogg, 2009;Bernstein, 2012;Manning, 2014), illustrating how changes in the configuration of space can disrupt and transform extant social practices in organizations with important consequences for temporal flexibility. This study thus offers additional empirical evidence of a relationship among physical space, social practices, and social cognition.…”
Section: Discussionmentioning
confidence: 99%
“…First, certain kinds of physical spaces can encourage risk-taking behaviors among employees. Several studies have shown that spaces providing isolation can allow employees to feel comfortable engaging in thick or emotive social interactions (Sundstrom, Burt, and Kamp, 1980; Becker et al, 1983; Carlopio and Gardner, 1992; Manning, 2014), collectively experimenting and learning new techniques (Bernstein, 2012), or covertly mobilizing for organizational change (Kellogg, 2009). Because flexible work policies represent a source of risk for employees’ reputations, it is possible that physical spaces that enable risk-taking might encourage employees to use these policies.…”
Section: The Flexibility Paradox: Flexible Work Policies Career Penamentioning
confidence: 99%
“…For an illustration, we move from the communities of Sierra Leone to the pediatric wards of two government hospitals in West Africa (Manning 2014). Nurses in these hospitals are trained to operate within a specific moral order, with clearly articulated rules and procedures for how to treat patients and interact with their family members.…”
Section: Moral Blurringmentioning
confidence: 99%